Parent's Knowledge, Attitude and Pattern of Care for Children with Epilepsy in Lagos, Nigeria - MA Salisu; IO Senbanjo; KA Oshikoya; MO Lamina; EO Alaje (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Background: Epilepsy is a common paediatric neurologic disorder associated with stigmatisation due to a lack of understanding of the disease and wrong beliefs. Objective: To assess parents' knowledge about epilepsy, attitude towards the disease and care for the affected child in Lagos, Nigeria. Methods: This was a descriptive cross-sectional study of parents of children with epilepsy presenting to the Paediatric Neurology Out-Patient Clinic in a tertiary facility between June and August 2019. Data collection was done using a semi-structured questionnaire. Results: A total of 112 parent-child pairs participated in this study. The mean age of the fathers and mothers were 44.9 ± 10.4 years and 37.9 ± 9.0 years, respectively. Most (98.2%) of the parents had at least a secondary level of education, and about half (42.9%) belonged to the upper socioeconomic class. About three-quarters (73.2%) of parents have heard about epilepsy before presentation at the clinic. Twenty-eight (25%) parents had misconceptions or no idea of the causes of epilepsy. About a third of the parents did not know the correct measures to be taken during seizure attacks. Three-quarters (76.8%) of children received prescribed medication regularly, and one of the reasons given for non-compliance with medications was poor effectiveness of the medications. (15.4%). Conclusions: The attitude and care of parents towards children living with epilepsy were poor. A period must be dedicated to educating all parents as soon as they present to the clinic with their children.